Efeito do carvacrol e do seu complexo de inclusão com β-ciclodextrina sobre a nocicepção induzida por células tumorais (S180) em roedores - Guimarães, Adriana Gibara (2014)
Throughout the history of the development of treatments proposed for pain, medicinal plants and their secondary metabolites have played a key role. However, even more effective therapeutic options for the treatment of painful conditions are necessary. In this sense, the present study aimed to evaluate the effect of the inclusion complex of β-cyclodextrin (β-CD) containing carvacrol, a phenolic monoterpene present in the essential oil of medicinal plants of the genus Origanum, Thymus (Lamiaceae), on the oncology nociception (induced by tumor cell sarcoma 180, S180) in experimental animals. This thesis is formed by three chapters, consisting of a review of patents and two regular papers. Initially, the review Terpenes and derivatives as a new perspective for pain treatment: a patent review was elaborated, which describes patents on the analgesic properties of terpenes and prospects created from these records. After conducting the experimental protocols, the article Evidence for the Involvement of descending pain- inhibitory mechanisms in the attenuation of cancer pain induced by carvacrol , a monoterpene of Origanum oil was constructed, in which it has been shown that carvacrol (CARV) reduces nociception induced by tumor cells (S180), decreases the number of Fos positive neurons in lamina I of the Lumbar spinal cord and activates the brain nuclei involved in the descending inhibitory pain pathway, such as the periaqueductal gray, nucleus raphe magnus and locus coeruleus. Subsequently, the inclusion complex consisting of carvacrol and β-cyclodextrin (CARV/β-CD) was developed and characterized physicochemically through the method of co-evaporation. CARV complexation was able to increase the time of the antinociceptive effects of this compound in animals with S180 in 15 hours and improved the pharmacological response at lower doses, in addition to promoting a clear increase in solubility and stability. These data formed the patent submitted and approved by the Center for Innovation and Technology Transfer (CINTEC UFS) and forms the scientific basis of the article Encapsulation of β-cyclodextrin in carvacrol improves the pharmacological response on cancer pain . From these findings, we conclude that the analgesic effect of carvacrol on cancer pain can be enhanced by employing inclusion complexes containing β-cyclodextrin and may represent an interesting object of further translational research and clinical trials in order clinical evidence to be obtained, which is necessary for the development of new drugs for cancer-associated pain management.